THE IMPLEMENTATION OF PROJECT BASED LEARNING TO IMPROVE THE COMPETENCES OF TEACHER CANDIDATES (Proceedings of the International Conference on Education, 2017)
Based on the legislation in Indonesia, the required competences of teachers in Indonesia include pedagogical, professional, social, and personality. As one of teacher candidate education institution, Chemistry Education Department, Islamic University of Indonesia contribute to produce competent teacher candidates. The department has developed course materials, learning strategies; system-oriented evaluation to develop student competence as chemistry teacher candidates. Project Based Learning (PBL) is an option that is applied to achieve these objectives. This study aims to describe the implementation of PBL towards the attainment of teacher candidates. Subjects were students of chemistry education level three in academic years of 2016/2017. The research instruments include project assessment, competency tests, observation sheets, and student satisfaction questionnaire. Learning is conducted in accordance with the stages in the PBL such as: start with the essential question, design a plan, create a schedule, monitor, and assess the outcome. The research data shows that PBL gives positive impact on the attainment of teacher candidates. Students also gave a positive response to the application of PBL. The data of assessment pedagogical, professional, social, and personality in consecutive is 1.6 (good categories), 1.3 (enough categories), 1.7 (good categories), 1.6 (good categories). The score of student assessment related to the implementation of PBL is 1.8 (good categories).
Keywords: Project Based Learning; Teacher Competence; Teacher Candidates